2018
DOI: 10.1155/2018/6716547
|View full text |Cite
|
Sign up to set email alerts
|

Angelica gigas Nakai Has Synergetic Effects on Doxorubicin-Induced Apoptosis

Abstract: Natural products are valuable sources for drug discovery because they have a wide variety of useful chemical components and biological properties. A quick reevaluation of the potential therapeutic properties of established natural products was made possible by the recent development of the methodology and improvement in the accuracy of an automated high-throughput screening system. In this study, we screened natural product libraries to detect compounds with anticancer effects using HeLa cells. Of the 420 plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The results showed that decursin is the main constituent of AGE. According to a previous study, the second peak in the UPLC assay may indicate decursinol angelate [8]. In this study, AGE and decursin showed growth inhibition and colony formation of PANC-1 and MIA PaCa-2 cells in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The results showed that decursin is the main constituent of AGE. According to a previous study, the second peak in the UPLC assay may indicate decursinol angelate [8]. In this study, AGE and decursin showed growth inhibition and colony formation of PANC-1 and MIA PaCa-2 cells in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that the extract of Angelica gigas Nakai contains decursin [8]. We first confirmed the presence of decursin in AGE by ultra-performance liquid chromatography (UPLC) assay conducted using AGE and decursin under the same conditions.…”
Section: Age and Decursin Inhibited Proliferation Of Panc-1 And Mia Paca-2 Cellsmentioning
confidence: 61%
See 1 more Smart Citation
“…Apoptosis has been shown to be one of the key processes in DOX-induced cardiac injury [4,8,23,24]. We observed few apoptotic cells in the CON and CON+L groups, but more apoptotic cells in the DOX group.…”
Section: Discussionmentioning
confidence: 46%
“…The cumulative and dose-dependent toxicity induced by DOX is harmful to nontumor tissues, and in myocardial tissue, DOX causes irreversible damage, which can lead to dilated cardiomyopathy, greatly limiting its clinical application [4,5]. Many mechanisms underlying DOX-induced cardiotoxicity have been discovered, including mitochondrial iron accumulation and related redox reactions, the activation of immunological reactions, histamine release, and DNA damage, and emerging research indicates a crucial role for apoptosis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%